Характеристика мікрофлори стоп у хворих із синдромом діабетичної стопи - Таран, Є. В.; Юзвенко, Т. Ю.; Гирявенко, О. Я.; Болгарська, С. В.; Славнов, В. М. (Clinical Endocrinology and Endocrine Surgery, 2012)
It is shown that the forms of neuropathic diabetic foot, accompanied by prolonged existence (over 2 months) of pressor plantar forefoot non-healing ulcers, there is colonization of hyperkeratosis surrounding the wound surface, involvement in the inflammatory process of soft tissues and bony structures (adjacent to the ulcer area), presence of mixed fungal and bacterial flora, where fungal component is represented mainly by opportunistic fungi. Foci of neuroosteoarthropathicn midfoot defeat in these cases also contain opportunistic fungi.